Chemokine receptor expression on dendritic cells is normal in HIV-infected patients with a stable response to ART, but chemokine levels remain elevated - Lee, S.; Fernandez, S.; French, M.; Price, Patricia (2011)
The development of strategies to optimize T-cell responses in previously immunodeficient HIV patients with a stable virological response to ART requires an understanding of the factors that affect responsiveness. Chemokines direct the migration of dendritic cells (DC) to non-lymphoid tissues infected by secondary pathogens and to lymph nodes where they prime T-cells. Quantitation of mRNA is a sensitive technique enabling assessment of chemokine receptors by CD14 + monocytes, myeloid (m)DCs, plasmacytoid (p)DCs, and M-DC8 + cells. MDC8 + cells invariably expressed less CCR2, CCR5, and CXCR4 than the other cells, but expression of CCR2, CCR5, CCR6, CCR7, CXCR3, and CXCR4 was similar in patients and healthy controls. However plasma levels of CXCL10, CCL5, and CCL2 remained higher in patients than controls. Overall, it appears that chemokine directed migration of DC may not limit immune responses in these patients. © 2011 Wiley-Liss, Inc.